Investigation of the relationship between the design and technological parameters of vibration and oscillating rollers - Shishkin E.A.; Ivanchenko S.N.; Sidorkov V.V.; Mamaev L.A.; Smolyakov A.A. (Научно-технический вестник Брянского государственного университета)
Simulation is an important step in the design of new road roller models. In the process of modeling, it is possible to exclude options that do not allow obtaining the optimal structure or parameters of the designed machine. To carry out this stage, it is necessary to have information about the range of values of the design parameters of the roller, the main of which is the operating weight. The mass per axle of a road roller depends on its operating mass and consists of the mass of the frame part and the mass of the drum, the value of which is required in the dynamic simulation of the vibrating drum-compacted material system. Manufacturers of road rollers do not give the drum weight in their technical documentation, so it is difficult to determine its value. In the proposed study, the analytical dependence of the drum mass on the technological parameters of the vibrating and oscillating roller was obtained, and the statistical analysis carried out showed that for calculations the drum mass can be taken equal to 20% of the operational roller mass. As a result of the analysis of the system of forces acting on the drum, it was found that with the same mass, the oscillating drum, in comparison with the vibration, develops a greater driving force. In addition, the impulse of the driving force of the oscillating drum is higher than the impulse of the vibratory drum. The research results can be used to simulate the interaction of a smooth drum of a road roller in the design of new machine models.